Semilunar vestibular technique: A novel procedure for multiple recession coverage (a report of two cases) - Nymphea Pandit; Inder Kumar Pandit; Deepika Bali; Shaifi Jindal (Wolters Kluwer Medknow Publications, 2015)
The procedures for root coverage have been greatly refined over the past few decades. Still as compared to the other periodontal surgical procedures, predictability of mucogingival procedures remains uncertain which is more in patients who present with multiple recessions or recession complicated with periodontal involvement. Techniques which claim success almost always involve a second surgical site. A novel technique avoiding second surgical site and good predictability for multiple recessions was described by Dr. P.D. Miller in a conference at Pune in 2011. A semilunar vestibular incision technique described by Dr. P.D Miller was performed on two patients who presented with multiple recessions in the maxillary anterior teeth. About 90-100% root coverage was observed when the patients were on a follow-up for 1-year with a significant increase in the vestibular depth. The semilunar vestibular incision technique used in two cases resulted in predictable root coverage with a good color blend, an esthetic marginal morphology and most importantly the avoidance of the second surgical site.